Control of Rice Stem Borer Scirpophaga sp. Using Trichogramma sp. - Lutfi Afifah; Fawzy Muhammad Bayfurqon; Siti Latifatus Siriyah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
This community services activity was conducted together with a partner that is Benong II Farmers Group, in the Kalibuaya Village, Telaga Sari, Karawang. The problem that faced by partners is a lack of understanding of plant pest organisms (OPT), especially plant pests and diseases, as well as a lack of knowledge about the natural enemies. Knowledge and skills of the Benong II Farmers Group in the Kalibuaya Village, Telaga Sari, Karawang regarding the management and control of rice stem borer that environmentally friendly, especially biological control using parasitoid Trichogramma sp. needs to be improved. The evaluation results show that counselling and training on the breeding of natural enemies Trichogramma sp. resulting in the development and progress of the behavior, attitudes, and skills of farmers. There are four main results of the research. The results are (1) farmer more understand of the use of biological agents for IPM-based rice pest and disease control; (2) want to implement the control of rice stem borer Scirpophaga sp. by using Trichogramma sp.; (3) more skilled in monitoring the presence or absence of pests in rice plantations in the field; and (4) more active in finding out to community service teams, farmer group leaders, and POPT / field extension officers about how to mass culture theTrichogramma sp. and it’s release techniques in the field.